Modelling long-term greenhouse gas mitigation pathways for Mongolia - Tsolmon Namkhainyam; Bavuudorj Ovgor; Dorjpurev Jargal; Christopher S Malley (Environmental Research Communications)
Mongolia’s faces substantial challenges to reduce its Greenhouse Gas (GHG) emissions due to reliance on coal to meet electricity, heat and other energy demand and large livestock emissions. Despite this, Mongolia has committed to reduce GHG emissions by 22.7% in 2030 compared to a baseline scenario. Greenhouse gas mitigation assessments for Mongolia have focussed on actions to achieve emission reductions by 2030, but not on the potential for further reductions over the longer-term. This study addresses this gap through the development of long-term (2050) GHG emission pathways for Mongolia. These pathways aim to inform what level of GHG reduction targets Mongolia could commit to for the period after its current target expires. Greenhouse gas emissions are quantified for historic years (2010–2019) for all major GHG emitting sectors, and projected to 2050 based on the population and economic forecasts. Finally, mitigation scenarios modelling implementation of 49 specific mitigation measures are developed, to quantify their emission reduction potential. Without mitigation, GHG emissions were estimated to increase by 67% and 139% in 2030 and 2050, respectively, compared to 2019 levels (39 million tonnes CO _2 -eq emissions). Implementation of the 49 mitigation measures could reduce GHG emissions by 40% in 2050 compared to the baseline. Therefore, post-2030, Mongolia could increase its climate change mitigation ambition. Renewable Electricity generation, and energy efficiency were the measures that could achieve the majority of these additional emission reductions. However, there remains a substantial gap between the emission reduction potential of technically feasible measures currently being considered in Mongolia’s climate change mitigation planning, and full decarbonisation.